FENOMENA KENAKALAN REMAJA DI DESA WONOREJO KABUPATEN SITUBONDO - Ariyanik, Siti; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2012)
This research was intended to determine and describe the behaviors of Toto Gelap (Togel)-addicted people in Kasiyan Village, District of Puger, Jember regency. The research used symbolic interactionism theory of Blumer. Togel activities done by the community are not always caused by economic reasons that make someone to do Togel gambling. Some reasons are by hobbies, lifestyle, and consideration as a determinant of social status. Besides, in determining Togel coupon, Togel-addicted people use unique ways by the mystical path. On the other hand, the things related to the mystique have been a habit, tradition, and belief handed down from generation to generation. The research used descriptivequalitative methods, and informants were determined by purposive sampling. Data collection methods used were structured observation, in-depth interviews, and documentation. Togel in Kasiyan Village, District of Puger, Jember Regency has been growing since the 2000s. Togel-addict group has some mystical behaviors, which include: dream interpretation, grandong (an activity done on a grave for getting signs/information from spirits), natural code, meditation, spirituality, and fortune-telling. Besides, Togel gambling has special functions and meanings for togel-addicted people as a source of income, a shortcut to debts settlement, and marketing strategies. Meanwhile, the meanings of Togel gambling for togel-addicted people are as a medium of channeling the desire to gambling, gambler togetherness tier, and a means of affirming the identity of gamblers. Keywords: addicts, togel, mystical behaviors.